Semi-automatic cloth bag making machine. (2020) - Arunkumar, S.; Suganeswaran, K.; Nithyavathy, N.; Gobinath, V.K.
Abstract: Plastic is considered as one of the greatest threat due to its use in carrying things which became a major aspect in polluting the environment in a exponential manner. Over years, these contaminants linger in the earth as landfills, defiling and polluting the environment, keeping it from replenishing the minerals, thus making it infertile [1] . At the end, productive fields becoming desolate and being abandoned. There is an urgent need for cotton carry bags, which can be produced in various sizes, despite the need to solve this issue. First the clothes are cut by the sewing scissors according to the measurements needed of the carrying bag and then the two opposite sides of the fabric are stitched and the thread is cut manually by the tailor. The proposed methodology suggested is to create a semi-automatic cloth bag producing system that produces the full cloth carry bag that automatically stitches the fabric and also produces slot in the cloth bag for carrying purposes. This new approach will help to resolve the drawbacks of the current approach and at minimum possible expense the cloth bag can be produced.